PENGARUH KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN PADA JASA PENGIRIMAN SICEPAT EKSPRES - Muhammad Arviandaffa Ghifary Aufarizi (2022)
The type of research conducted by the researcher is quantitative research which aims to determine the effect of service quality on customer satisfaction, the effect of customer satisfaction and service quality on customer loyalty, and the indirect effect of service quality on customer loyalty through customer satisfaction. This research is quantitative data with primary data sources. The population of this research is DKI Jakarta which has an online store, using SiCepat Express to send packages in E-Commerce. The sample used is 100 respondents. The sampling technique used non-probability sampling with purposive sampling method. The data collection carried out by this study was done by using an online questionnaire using Google Form facilities such as line, WhatsApp and Instagram. This study uses the SEM method with the software used is SmartPls 3.0. The research obtained the results, namely: the service quality variable has a positive and significant effect on customer satisfaction with an original sample value of 0.790. Customer satisfaction has a positive and significant effect on customer loyalty with an original sample value of 0.346. Service quality has a positive and significant effect on customer loyalty with an original sample value of 0.550. Service quality indirectly has a positive and significant effect on customer loyalty through customer satisfaction with an original sample value of 0.273.